1989
DOI: 10.1007/bf01658399
|View full text |Cite
|
Sign up to set email alerts
|

Complications and hazards of gastrointestinal endoscopy

Abstract: The diagnostic and therapeutic contribution of fiberoptic endoscopy to the advancement of the knowledge of gastrointestinal disease and to its proper management is already established. Technical refinements in the new instruments and extensive acceptance of the advantages of the method makes fiberendoscopy a procedure widely used throughout the world. Therefore, the appreciation of its potential risk of complications and hazards is justified. This review summarizes the complications and hazards of fiberoptic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
13

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(75 citation statements)
references
References 85 publications
4
58
0
13
Order By: Relevance
“…Based on findings for cancer, colonoscopy sensitivity was lowered for proximal lesions 32,33 . Colonoscopy complication rates were 0.00014 for death, 0.0012 for perforation, and 0.0003 for hemorrhage [34][35][36][37] . Sigmoidoscopy parameters were assumed to be the same as those for colonoscopy in the distal colon and rectum.…”
Section: Test Characteristicsmentioning
confidence: 99%
“…Based on findings for cancer, colonoscopy sensitivity was lowered for proximal lesions 32,33 . Colonoscopy complication rates were 0.00014 for death, 0.0012 for perforation, and 0.0003 for hemorrhage [34][35][36][37] . Sigmoidoscopy parameters were assumed to be the same as those for colonoscopy in the distal colon and rectum.…”
Section: Test Characteristicsmentioning
confidence: 99%
“…Most complications and deaths resulting from upper gastrointestinal endoscopy are cardiopulmonary in nature [4,5]. Many of these may be related to the use of intravenous sedation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that these small polyps, even with the histologic characteristics of adenoma, rarely have foci of malignancy (less than 1 in 1000) [17][18][19][20][21]. Such data would justify the opinion of authors who maintain that colonoscopy should not be routinely used for such lesions, since the diagnostic benefits may not always justify the associated risks, even though minimal [22].…”
Section: Discussionmentioning
confidence: 99%